Conducting Business Activity in Poland by Foreign Nationals from Ukraine - Jan GOLA (Communications of International Proceedings, 2025)
The article concerns the conduct of business activity in Poland by foreign nationals from Ukraine. It cites the normative bases for such a possibility that emerged after Russia’s unlawful aggression against Ukraine. It also presents the economic aspect of the increased presence of the entities referred to in the title in Poland. The objective of this article is to examine the mechanisms governing the undertaking and pursuit of economic activity in the territory of the Republic of Poland by foreign nationals from Ukraine, considered within the framework of one of the fundamental principles of public economic law—namely, the principle of safeguarding the political and economic interests of the state in its relations with foreign actors. This principle entails a complex interplay between regulatory instruments and economic policing measures. The author argues that the armed aggression initiated by the Russian Federation against Ukraine in 2022 has substantially contributed to an increase in the number of Ukrainian business entities operating in Poland. Their presence exerts a favourable influence on competitive conditions in the Polish market and thereby supports the country’s broader economic development. In particular, these entities mitigate labour market shortages, stimulate growth in gross domestic product, and enhance consumption dynamics. Moreover, Ukrainian foreign nationals contribute to strengthening the innovative capacity of the Polish economy. The article applies the formal-dogmatic method and a functional method of analysis, which makes it possible to study law in action.
Keywords: business activity; foreign persons; Ukraine; economy; public economic law; economic free-dom